Empowering Women Entrepreneurs: A Comprehensive Analysis of their Impact in G20 Economies - Kumar, Saurav (Apex Journal of Business and Management, 2024)
The evolution of women in entrepreneurship over the past five decades has been marked by significant progress and challenges. Despite historical discrimination and gender inequalities, women have increasingly ventured into entrepreneurship, showcasing their strength as innovators and business leaders. This transformation is particularly evident in developing nations, where women entrepreneurs have not only fueled market growth but also enhanced employment opportunities. However, achieving gender equality in entrepreneurship remains a global issue, with only a few countries attaining parity in this domain. Women-owned businesses predominantly operate in small to medium enterprises, focusing on sectors like fashion retail, beauty cosmetics, and food services, especially in Africa and Asia. While progress has been made, challenges persist for women entrepreneurs globally. The journey of women in entrepreneurship highlights their resilience and innovation but also emphasizes the need to address remaining barriers to foster gender equality on a global scale. The research is the first collective study on role of women entrepreneurs in all 21 member nations of the G20 economic forum.